Plan Parcial de Mejoramiento Integral: Moravia un proceso de reconstrucción con sabor a memoria. (2016)
Those who were travelling the corridors and corridors of the University of Antioch at the end of the decade of 1970 and beginning of her of 1980, must remember a stinking smell that was invading the classrooms, a smell of garbage that was coming from that nearby knob where the wastes of the city were settling and of which the bad languages were speaking about children who were fighting with the turkey-buzzards for remains of food. There, where for incredible that seemed people were living, probably with the only opportunity to possess a ceiling where to sleep. During the accomplishment of the investigation a documentary was obtained as final product applying methods of investigation, where by means of a participative way of the community where Moravia was confirmed by means of opinions, surveys, and observations of the involved ones by the stipulated by the mayoralty in the process of the Plan of Territorial Classification - in forward POT - in the neighborhood, commune 4 Medellin. At present the sector has evolved in 3 thematic axes on which it centred on the project being documentary " Partial Plan of Integral Improvement: Moravia a process of reconstruction with flavor to memory " legitimate witness who across images, interviews, photos of file, cultural samples, between other activities manages contextualizar as his inhabitants they have appropriated and been determinant for this initiative that arose from the mayoralty of Medellin from the year 2004.